Numerical Analysis of Reinforced Concrete Corbels Using Concrete Damage Plasticity: Sensitivity to Material Parameters and Comparison with Analytical Models - Neuberger, Ygor Moriel; Andrade, Maykon Vinicius; de Sousa, Alex Micael Dantas; Bandieira, Mariana; da Silva Júnior, Edivaldo Pereira; dos Santos, Herisson Ferreira; Catoia, Bruna; Bolandim, Emerson Alexandro [UNESP]; de Moura Aquino, Vinicius Borges [UNESP]; Christoforo, André Luis; de Araújo Ferreira, Marcelo (MDPI, 2023)
The Concrete Damage Plasticity (CDP) model is a widely used constitutive model to represent the non-linear behavior of concrete in numerical analysis. However, a limited number of studies compared the level of accuracy of numerical models with the main code provisions from the literature. In addition, the influence of CDP material parameters on the structural behavior of corbels was scarcely studied. This study proposes to evaluate the ability of numerical models using CDP to represent the structural behavior of corbels regarding the ultimate load, reinforcement deformation and failure mechanism. In addition, we compared the predictions of the numerical models with the ones from design code expressions regarding the ultimate capacity. For this, three test results of corbels from the literature were evaluated with numerical models using the CDP, as well as with analytical models from different code provisions. A sensitivity analysis—by changing the dilation angle (ψ) and shape factor (Kc)—was performed. The comparison between tested and predicted resistances with the proposed numerical modeling choices was equal to 1.04 with a coefficient of variation of 11%. On the other hand, the analytical models evaluated overestimated the corbel capacity by more than 62%, on average. Therefore, the proposed modeling choices provide better predictions of ultimate capacity than the evaluated analytical models and can be used to assess the corbel design under more complex boundary conditions.
Keywords: concrete damage plasticity (CDP); numerical modeling; region of stress discontinuity (D region); reinforced concrete corbels